DEMs and SAR Images - Teng, H.-T.; Tay, L.-T. (2006)
The use of fractal dimension as a discriminator in SAR images for analyzing surface roughness has been proved to be effective. Fractal dimension has also been used as an indicator for terrain surface roughness in DEM. However, a single fractal dimension is not a very useful measure. In this paper, we have proposed a surface roughness index for estimation of image surface roughness. Promising results are shown for applications in DEM of different altitude ranges and SAR image of different landuse classes.